Sistem Informasi Akuntansi Penggajian Studi Kasus Pada PT. Mandiri Jaya Sembilan - Ima Wahyu Dewi Saputri; Fitri Komariyah (CV ODIS, 2022)
The purpose of this research is to understand the payroll accounting system at PT. Mandiri Jaya Sembilan. The descriptive method is used in this research by using interviews, documentation, and observation techniques. The results of this research state that the application of the payroll accounting system at PT. Mandiri Jaya Sembilan is good enough. The accounting department is responsible for the payment and remuneration of workers' salaries and is responsible for implementing control over the filling and recap of the attendance list of workers so as to minimize irregularities in employee payroll.